2018
DOI: 10.3389/fmicb.2018.00997
|View full text |Cite
|
Sign up to set email alerts
|

Microscale Biosignatures and Abiotic Mineral Authigenesis in Little Hot Creek, California

Abstract: Hot spring environments can create physical and chemical gradients favorable for unique microbial life. They can also include authigenic mineral precipitates that may preserve signs of biological activity on Earth and possibly other planets. The abiogenic or biogenic origins of such precipitates can be difficult to discern, therefore a better understanding of mineral formation processes is critical for the accurate interpretation of biosignatures from hot springs. Little Hot Creek (LHC) is a hot spring complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(48 citation statements)
references
References 80 publications
1
47
0
Order By: Relevance
“…Although associated with micrite, filament-like porosity in the Maquinchao samples seems to be unrelated to porosity. Furthermore, micro-boring organisms can be a source of micritization (Bathurst, 1966;Kraus et al, 2018) but this does not appear to be the case in this study as the micrite is very homogeneous and, therefore, unlikely to result from micro-boring. In the analysed samples, filaments were observed that are mostly vertically erected with no ramifications.…”
Section: Biotic Versus Abiotic Processesmentioning
confidence: 76%
See 1 more Smart Citation
“…Although associated with micrite, filament-like porosity in the Maquinchao samples seems to be unrelated to porosity. Furthermore, micro-boring organisms can be a source of micritization (Bathurst, 1966;Kraus et al, 2018) but this does not appear to be the case in this study as the micrite is very homogeneous and, therefore, unlikely to result from micro-boring. In the analysed samples, filaments were observed that are mostly vertically erected with no ramifications.…”
Section: Biotic Versus Abiotic Processesmentioning
confidence: 76%
“…Filaments of around 5-10 ”m width have been identified as different microorganisms, mostly cyanobacteria such as Oscillatoria, Phormidium, Schizothrix or Rivularia, especially in fluviatile and lacustrine systems (Freytet & Plet, 1996;Freytet & Verrecchia, 1998). Nevertheless, Kraus, Beeler, Mors, Floyd, and Stamps (2018) has demonstrated that vertical tubular porosity can be associated with micro-boring by microorganisms. Although associated with micrite, filament-like porosity in the Maquinchao samples seems to be unrelated to porosity.…”
Section: Biotic Versus Abiotic Processesmentioning
confidence: 99%
“…Libraries of bacterial, archaeal, and eukaryotic small subunit (SSU) rRNA gene fragments were amplified from each DNA extraction using a single set of PCR with primers that spanned the SSU rRNA gene V4/V5 hypervariable regions between position 515 and 926 (E. coli numbering) as described previously (Parada et al, 2015;Kraus et al, 2018). The primers used were selected to evenly amplify all three domains of life simultaneously (Parada et al, 2015).…”
Section: In Situ Incubation and Sampling Of Corrosion Couponsmentioning
confidence: 99%
“…These primers produced two amplicons, a ~400 bp fragment for bacteria and archaea, and a 600 bp fragment for eukaryotes. The forward primer 515F-Y (5’- GTA AAA CGA CGG CCA G CCG TGY CAG CMG CCG CGG TAA-3’) contains the M13 tag (underlined) fused to the 5’ end of the forward primer (41). The reverse primer 926R (5’-CCG YCA ATT YMT TTR AGT TT-3’) was unmodified from Parada et.…”
Section: Methodsmentioning
confidence: 99%